Casos y cosas: semanario popular (Vol. 2, No. 70) - Imprenta La Region (My University, 1921)
SPANISH: Incluye: Crueldad inaudita, Luces de bengala, Los de la "Troncha" en acción, Lo que yo he visto, Apuntes y comentarios, Buzón, Las hojas del calendario

ENGLISH: Includes: Unheard-of cruelty, Flares, The "Troncha" in action, What I have seen, Notes and comments, Mailbox, Calendar leaves.
Cases and things: popular weekly magazine (Vol. 2, No. 70)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas